KH. Ahmad Shofawi (1928-1962 M); Cleric and Batik Merchant Who Contributed Greatly to Islamic Da'wah in Surakarta - Bistara , Raha; Nufus , Firindah (Al-Insyiroh: Jurnal Studi Keislaman, 2022)
This article wants to discuss how the dakwah patters carried out by the Kiai Shofawi. As a scholar and a batik merchant, Kiai Shofawi chose to deliver of sermon, not verbal. Therefore, this system make Islam is more easily accepted in all levels of society. Islam a solution for those people who really need it. This was proven by Kiai Shofawi as a generous merchant and polite scholar. His mission is implemented through the world of batik commerce and build a modern formal educational institutions. This proves that dakwah deliver if sermon is successful, Islam can be accepted happily whitout any violence. By using the heuristic method with examing the studied, literature, and field sources. This study expected to answer the questions which are present regarding the role of the Kiai Shofawi in spreading Islam in Surakarta. This is complicated, because there is little previous studies especially discussed the role of this particular scholar. The presence of islamic educational institutions such as Ta’mirul Islam and Al-Muayyad islamic boarding school show that the development of Kiai Shofawi missions’ in Surakarta is successful. This has eliminated scholars who are inleketual and intellectual in the style of islamic scholar.